A Modified Closed-Open Approach as Part of a Graduated and Integrative Approach to Rhinoplasty - Röjdmark, Jonas; Mouchammed, Agko (Indian Journal of Plastic Surgery, 2019)
Introduction Open versus closed approach in rhinoplasty is a frequently debated topic in aesthetic plastic surgery. Although good results can often be achieved with either technique, both have unique advantages and disadvantages. In this investigation, we present our experiences of a modified closed-open approach that has been applied on 482 complex primary and secondary rhinoplasties. Three representative cases are described in more detail.Materials and Methods The procedure begins as a closed approach through an intracartilaginous incision allowing cephalic trimming of the lateral crura, dorsal rasping, and/or excision. Patients requiring extensive nasal tip maneuvers are subjected to exposure of the alar cartilage framework through a transcolumellar/limited marginal incision. This provides not only adequate exposure of the alar cartilages but also easy access to the septum.Conclusion In our hands, this approach is easy and expeditious. It requires less tip dissection, and therefore may avoid the prolonged postoperative edema that is often a consequence of open or extended closed tip delivery approaches.
Keywords: modified closed-open approach; open and closed approaches; rhinoplasty